Penerapan Media Pembelajaran Peta Tiga Dimensi Melalui Pembelajaran Tutor Sebaya Untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SDN Banjaran Kecamatan Driyorejo Kabupaten Gresik - Ery Rahmawati; Galuh Kartika Dewi (Jurnal Ilmiah Mandala Education (JIME), 2020)
This study aims to identify and describe the social studies learning outcomes and student activeness after applying the three-dimensional map learning media through peer tutoring learning for fourth grade students of SDN Banjaran, Driyorejo District, Gresik Regency. This research on learning improvement is supported by the ability of grade IV students at SDN Banjaran Driyorejo-Gresik who do not meet the predetermined learning completeness criteria. From this problem, learning improvement is carried out in two cycles using the Classroom Action Research method by applying three-dimensional map learning media through peer tutoring learning. There are four stages in each cycle, namely planning, implementing, observing, and reflecting activities. The results showed that there was an increase in the average student learning outcomes from pre-cycle 62.12 to cycle I of 75.19, and the result of cycle II to reach 84.14. Classical completeness of student learning outcomes also increased from 23.81% pre-cycle to 62.12% first cycle to second cycle of 92.31%. Student learning activities also increased from pre-cycle by 51% then cycle I 72% and cycle II reached 87%. Thus, it can be concluded that the application of three-dimensional map learning media through peer tutoring can improve social studies learning outcomes in fourth grade students of SDN Banjaran, Driyorejo-Gresik